The Road to Sustainability in Dentistry - Is the Reuse of Sterilization Pouches Viable? - Catarina Amaral; Mariana Henriques; Fernanda Gomes; Pedro Mesquita; Maria João Ponces (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: To answer the question: Can sterilized pouches be used a second time while maintaining their sterility conditions? Methods: This investigation tested paper/plastic sterilization pouches divided into three groups: experimental group - twice-used pouches; negative control group - once-used pouches; and positive control group - environmentally contaminated pouches. In the experimental group, pouches were opened, a gauze dressing was placed into them, and they were sterilized again, representing the reuse of the pouches (second sterilization cycle). After the sterilization cycle, samples were stored for 1 day (T0), 7 days (T1), 31 days (T2), and 153 days (T3). Positive control group pouches were opened and exposed to contamination in the storage environment. After the specified storage period, the experimental and negative control groups' pouches were opened, and the gauze dressings were removed aseptically. All gauze dressings of all groups, including the positive control group, were incubated in Petri dishes with nutrient agar at 37°C for 3 days. After incubation, the Petri dishes were inspected, and the microbial contamination was assessed and classified as present or absent. Results: The experimental group's Petri dishes showed no sign of contamination. The same happened to the negative control group. The positive control group's Petri dishes presented microbial contamination. The same results were obtained for all incubation times. Conclusions: This study showed that sterilization pouches could be used a second time while maintaining sterility and integrity conditions, even for extended periods (153 days - 5 months of storage).